A Stretchable Nanogenerator with Electric/Light Dual‐Mode Energy Conversion. Issue 18 (28th June 2016) - Fang, Huajing; Wang, Xiandi; Li, Qiang; Peng, Dengfeng; Yan, Qingfeng; Pan, Caofeng
Abstract : As an alternative technology, stretchable electronics attract long‐lasting attention. A newly‐designed stretchable nanogenerator with unique dual‐mode energy conversion is reported. The ability of converting the input mechanical stimuli to either electric or light output is achieved by monolithically integrating a transparent single‐electrode triboelectric nanogenerator (S‐TENG) with a ZnS based mechanoluminescence (ML) composite. This stretchable device with versatile functions promotes the development of the smart systems to efficiently and diversely utilize ubiquitous mechanical energy and demonstrates great potential for artificial e‐skins. Abstract : A stretchable nanogenerator with the unique dual‐mode energy conversion is demonstrated. It has the ability of converting the input mechanical stimuli to either electric or light output. The device is achieved by monolithically integrating a transparent single‐electrode triboelectric nanogenerator with a ZnS based mechanoluminescence composite.